2014
DOI: 10.3892/mmr.2014.2726
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lactate dehydrogenase A by microRNA-34a resensitizes colon cancer cells to 5-fluorouracil

Abstract: 5-Fluorouracil (5-FU) chemotherapy is widely used in the treatment of advanced colon cancer. However, the development of resistance to 5-FU is a significant obstacle to successful treatment. MicroRNA-34a (miR-34a) has been reported to be downregulated in a number of tumor types and has also been shown to act as a tumor suppressor. However, the mechanisms underlying the biological effects of miR-34a in chemoresistance remain unclear. The present study showed that the expression of miR-34a is downregulated in 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 28 publications
4
48
0
Order By: Relevance
“…We found that miR-34a expression was decreased in T cells, which contributed to the increase in LDHA in human GC TILs. Several studies have revealed that LDHA is one of the target genes of miR-34a in different cancer tissues including breast cancer and colorectal cancer (CRC) [15,16,21]. Our results also indicated a similar outcome in that miR-34a downregulated LDHA expression in T cells.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found that miR-34a expression was decreased in T cells, which contributed to the increase in LDHA in human GC TILs. Several studies have revealed that LDHA is one of the target genes of miR-34a in different cancer tissues including breast cancer and colorectal cancer (CRC) [15,16,21]. Our results also indicated a similar outcome in that miR-34a downregulated LDHA expression in T cells.…”
Section: Discussionsupporting
confidence: 80%
“…Lactic acid has the formula CH 3 CH(OH)CO 2 H. The anion lactate CH 3 CH(OH)CO 2 − is the predominant moiety present in the human body, as the pKa of the lactate/lactic acid pair is 3.8 [15,17,18]. Pyruvate is the final product of glycolysis, yielding two moles of ATP for each molecule of glucose in the process [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is down-modulated in colorectal cancer (CRC) (100). In 5-Fluorouracil (5-FU)-resistant colon cancer cells ectopic expression of miR-34a inhibited cell growth and attenuated the resistance to 5-FU through down-regulation of SIRT1 and E2F3 (101), inhibition of LDHA (102) and of c-Kit, thus reducing stem cell factor (SCF)-induced migration/invasion (103). Yang et al demonstrated that miR-34 targets BCL2 and sensitizes HCC cells to sorafenib (104).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%
“…Like let-7c, also present in this subnetwork, let-7b resulted important for development of 5-FU chemoresistance in RCC (221). miR-34a also plays a role in resistance to 5-FU and to vemurafenib (102, 103, 388). The expression profile of lncRNAs was investigated in 5-FU-resistant colon cancer cell lines and snaR was confirmed to be downregulated (389); this loss increases cell viability after 5-FU treatment, suggesting that this lncRNA has a potential role as a negative regulator in drug response (390).…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%